Transparent and complete reporting of confounding in observational research - Henrik Larsson (Wiley, 2022)
Abstract Improved understanding of causal risk factors for child and adolescent mental health problems are dependent on observational research. Although confounding is a major limitation of observational research, this problem is widely ignored in the reporting and dissemination of findings from observational studies in psychiatric journals. There is clearly a need for improved reporting of confounding and more careful interpretation of observational research in psychiatry.